PENDAMPINGAN PEMBENTUKAN PAKET WISATA MANCING DAN REKREASI PULAU GELASA DESA BATU BERIGA - Feni Kurnia; Prayogo Walton, Erick; Rajab Vebrian; Nurjanah; Fitri Apriani; Yurdayanti; Dzihan Khilmi Ayu Firdausi (AbdiMuh : Jurnal Pengabdian Masyarakat, 2021)
Bangka Belitung is one of the archipelagic provinces that has a lot of natural tourism potential. The position of the province which is surrounded by the ocean makes many local people have a hobby of fishing, as evidenced by the many livelihoods and fishing shops that are spread, one of which is on Gelasa Island, Batu Beriga Village. Gelasa Island is one of the small islands located in the Province of the Bangka Belitung Islands, especially in Central Bangka Regency. This natural potential which is very much but still unexplored is one of the opportunities to be developed into a tourist attraction, such as fishing tourism. This service is focused on Pokdarwis and the Batu Beriga Village Fisherman Group. This activity aims to promote and develop the tourism aspect of fishing tourism activities on Gelasa Island, Batu Beriga Village, to become a mainstay tourist attraction on Bangka Island. The problem-solving methods used include: a) conducting a centralized group discussion (Focus Group Discussion), b) counseling and assistance in the preparation of tour packages, c) making media for socialization and marketing of glass island tour packages. From the implementation of this activity, participants received knowledge and guidance on the management of fishing tourism objects and tourism business management, as well as the formation of several tour packages on Gelasa Island, Batu Beriga Village.